Alpha Precision Turning and Engineering Sdn Bhd / Nooraina Fatihah Abu Bakar - Abu Bakar, Nooraina Fatihah (Universiti Teknologi MARA, Perlis, 2024)
This report is prepared for the Industrial Training from Universiti Teknologi Mara Cawangan Perlis. This paper consists of my industrial training from 4th September 2023 until 16th February 2024 for 6 months at Alpha Precision Turning and Engineering Sdn Bhd, Kulim Kedah. Thank you to my supervisor, Mr. Khairil Nadzrie, my advisor Miss Rozihanim Binti Shekh Zain and my examiner Dr. Chen Jen Eem who always support and shared knowledge with me. All this effort helps me to go through my industrial training become exciting and entertaining. I am assigned to the Human Resource Department to helps human resource officer with daily task, documentation, training and recruitment. Besides that, I keen to learn new knowledge every single day and gain experience through it to become more professionalism as I believe it will be useful for my future career. Furthermore, this report consists the study of Determinants of Capital Structure of Construction Industry in Malaysia. In the nutshell, I have admitted that the learning and experiences in this company really leads me to have better understanding of how to adapt in new environment and to building confidence in yourself.